But… How Helpful is That? Parents’ Views on the Helpfulness of Selected Resources When Making Educational Decisions for Their Young Children with Disabilities - Ruiz, María Isolina; Flynn-Wilson, Linda; Giovingo, Lauren; Wilson, Philip G. (Journal of the American Academy of Special Education Professionals, 2019)
Q-methodology was used to explore parents’ views on the helpfulness of selected resources when making educational decisions for their young children with disabilities. Parents’ determination to get what was best for the child and school staff who understood the child’s disabilities averaged the highest scores. Children’s age and type of disability seemed to influence parents’ perceptions of the helpfulness of specific resources. However, participants agreed that each one of the selected resources could be helpful to them at some point in their journey to secure adequate education and services for their children. By-person factor analysis identified three distinctive viewpoints on the helpfulness of resources presented to participants: a) using a balanced combination of internal and external resources, b) preference for internal or within-parent resources, and c) a focus on external resources. Parents suggested other resources that they thought would help them when making decisions about their children’s education.